2021
DOI: 10.1002/1878-0261.13020
|View full text |Cite
|
Sign up to set email alerts
|

DDRugging glioblastoma: understanding and targeting the DNA damage response to improve future therapies

Abstract: Glioblastoma is the most frequently diagnosed type of primary brain tumour in adults.These aggressive tumours are characterised by inherent treatment resistance and disease progression, contributing to ~190,000 brain-tumour related deaths globally each year. Current therapeutic interventions consist of surgical resection followed by radiotherapy and temozolomide chemotherapy, but average survival is typically around 1 year, with less than 10% of patients surviving more than 5 years. Recently, a fourth treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 257 publications
0
13
0
Order By: Relevance
“…However, studies have recently shown that MGMT overexpression is not the only determinant contributing to GBM resistance to TMZ [5]. Other factors, such as the advent of GSCs, overactivation of DNA repair pathways, favorable autophagy, decreased drug influx and increased drug efflux, facilitate drug resistance in TMZ in addition to MGMT overexpression [46][47][48][49][50][51]. GSCs exhibit the capacity for self-renewal, immortal propagation and multilineage differentiation [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have recently shown that MGMT overexpression is not the only determinant contributing to GBM resistance to TMZ [5]. Other factors, such as the advent of GSCs, overactivation of DNA repair pathways, favorable autophagy, decreased drug influx and increased drug efflux, facilitate drug resistance in TMZ in addition to MGMT overexpression [46][47][48][49][50][51]. GSCs exhibit the capacity for self-renewal, immortal propagation and multilineage differentiation [52].…”
Section: Discussionmentioning
confidence: 99%
“…In the SSB, PARP1 plays a central role in the detection and repair of the pathway (Ref. 9). SSB and base modification form multiple DNA lesions, favouring a change in base-pairing properties and causing spontaneous mutations (Ref.…”
Section: Dna Damage Response Induced By Temozolomide and Radiotherapymentioning
confidence: 99%
“…DSBs are repaired through two mechanisms, the NHEJ and HR DNA repair pathways (Ref. 9). The HR mechanisms takes place in late G1 and G2 phases and is using the sister chromatid as a DNA replication template to correct the damage (Refs 9, 68).…”
Section: Dna Damage Response Induced By Temozolomide and Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“… 4 In 2016, there were 330 000 CNS cancer cases, particularly brain tumors. 5 Since currently brain tumors lead to 190 000 deaths per year, 6 there is huge demand to find therapies that allow a better understanding of tumour cell behavior and, subsequently, implementation of targeted therapy.…”
Section: Introductionmentioning
confidence: 99%